Keragaman Genetik Antar Individu Bulu Babi (Tripneustes gratilla) di Pantai Rendani Kabupaten Manokwari - Firda, Wahyuma; Toha, Abdul Hamid A.; Mudjirahayu, Mudjirahayu; Dailami, Muhammad (Journal of Tropical Diversity, 2025)
Understanding the genetic diversity of sea urchins is essential for studying species diversity and the genetic relationships among species and individuals. The primary objective of the research was to determine the genetic diversity of sea urchins from Rendani Waters, Manokwari Regency. Specifically, the study aimed to identify the species of sea urchins, assess their nucleotide diversity and composition, measure genetic distances, and explore the kinship relationships between individual sea urchins. The research used a descriptive method and was conducted from November to December 2022. The species identification, based on genetic analysis, revealed that all samples belonged to T. gratilla, with a 99.20-100.00% similarity to the reference species. Genetic diversity among individual samples was found to be relatively low. The nucleotide composition showed an average GC content of 39.34-40.34%, which was lower than the AT content (53.87-60.66%). The genetic distance between the samples ranged from 0.00 to 0.07. A phylogenetic tree, constructed from the data, grouped all samples into two clusters with bootstrap values of 62/54.